Cirrhosis of liver is a risk factor for gallstone disease - Shirole, Nikhil U.; Gupta, Sudhir J.; Shah, Dharmesh K.; Gaikwad, Nitin R.; Sankalecha, Tushar H.; Kothari, Harit G. (International Journal of Research in Medical Sciences, 2017)
Background: Gallstones are common clinical finding in general population. Mean prevalence rate in Indian population is 4-5%. The prevalence of gallstones is found to be high in cirrhotic patients compared to the general population in some western studies. Cause of this increased prevalence however is not known. Aim of the study was to evaluate prevalence of the gall stones in the cirrhotic patients, assess risk factors in cirrhotic patients and clinical presentation. Methods: This is the cross sectional observational study, included cirrhotic patients (compensated or decompensated). Risk factors for gallstone formation (age, gender and diabetes mellitus), characteristics of liver cirrhosis (etiology, Child Turcotte Pugh class, hypersplenism and varices) and clinical presentation were assessed in all cirrhotic patients with gallstones. Results: 336 patients with liver cirrhosis are included in this study; 201 (59.80%) male and 135 (40.2%) female. Mean age of the patients is 44.95±13.1 years. Overall prevalence of gall stones was 12.8% (43/336). Out of 43 patients, 23 (53.5%) are male and 20 (46.5%) are female. As child status progresses from A to B to C, prevalence of gall stone increases, with 60.46% (26/43) of gall stones occurring in the patients with CTP class C. Only 8 (18.6%) patients had gallstone related symptoms while rests were asymptomatic. 5 (11.6%) had concurrent CBD stones. Cholecystectomy was possible in only 2 patients with symptomatic gallstones. Conclusions: The prevalence of gall stones in cirrhotic is higher than general population which increases with the severity of liver cirrhosis. Most cirrhotic patients are asymptomatic for gallstones.